Improving the technology of obtaining highquality castings from steel in sand-clay molds - Kholmirzaev Nozimjon; Khasanov Jamshidbek; Abdullayev Baxodirjon; Saidkhodjaeva Shokhista; Bektemirov Abdujalol; Sadikova Nargiza; Yusupov Bekzod; Nosirkhujaev Ibrokhim Sodik; Nurdinov Zokirjon (E3S Web of Conferences, 2024)
This article examines the technology for producing high-quality steel and alloy castings in sand-clay molds. The optimization of the sandclay compound mold composition is explored, focusing on bentonite and kaolin clays as binders. The mold composition is refined based on the research conducted on these binding clays, resulting in the production of gas-free cast products. Additionally, the gas permeability of the sand-clay molds increased by 14-16%. The study also presents a test analysis of the gas permeability property, a crucial aspect of sand-clay mold quality. Furthermore, a mathematical model of the process was developed from the research findings to predict gas permeability values with varying amounts of binding clays, eliminating the need for further testing.